Evolución y características del traspaso del tipo de cambio a precios en México - Daniel Angeles Galvan; Josué Fernando Cortés Espada; Daniel Sámano (Banco de México, 2019)
– This paper analyzes the exchange rate pass through to consumer prices in Mexico using different methodologies. First, we estimate Vector Autoregressive Models (VAR). Subsequently, we estimate Autoregressive Distributed Lags Models (ARDL) in order to make a long run analysis. In particular, we find that the exchange rate pass through to consumer prices is low and has barely changed in relation with the findings in previous studies. We also estimate that when the economy grows above its long-run trend, the point estimation of the exchange rate pass through is larger on average. Finally, we provide some evidence of asymmetry in the exchange rate pass through, that is, the point estimation of the exchange rate pass through is greater when there is a depreciation than when there is a currency appreciation. It should be noted that in the long run analysis these results are preserved.
Keywords: C22; C32; E31; F31; F41; 330; Depreciation; Inflation; Exchange Rate Pass Through; Asymmetries